Interval versus continuous training with identical workload: physiological and aerobic capacity adaptations - de Araujo, G G; Gobatto, C A; Marcos-Pereira, M; Dos Reis, I G M; Verlengia, R (Physiological research, 2015)
The interval model training has been more recommended to promote aerobic adaptations due to recovery period that enables the execution of elevated intensity and as consequence, higher workload in relation to continuous training. However, the physiological and aerobic capacity adaptations in interval training with identical workload to continuous are still uncertain. The purpose was to characterize the effects of chronic and acute biomarkers adaptations and aerobic capacity in interval and continuous protocols with equivalent load. Fifty Wistar rats were divided in three groups: Continuous training (GTC), interval training (GTI) and control (CG). The running training lasted 8 weeks (wk) and was based at Anaerobic Threshold (AT) velocity. GTI showed glycogen super-compensation (mg/100 mg) 48 h after training session in relation to CG and GTC (GTI red gastrocnemius (RG)=1.41+/-0.16; GTI white gastrocnemius (WG)=1.78+/-0.20; GTI soleus (S)=0.26+/-0.01; GTI liver (L)=2.72+/-0.36; GTC RG=0.42+/-0.17; GTC WG=0.54+/-0.22; GTC S=0.100+/-0.01; GTC L=1.12+/-0.24; CG RG=0.32+/-0.05; CG WG=0.65+/-0.17; CG S=0.14+/-0.01; CG L=2.28+/-0.33). The volume performed by GTI was higher than GTC. The aerobic capacity reduced 11 % after experimental period in GTC when compared to GTI, but this change was insignificant (19.6+/-5.4 m/min; 17.7+/-2.5 m/min, effect size = 0.59). Free fatty acids and glucose concentration did not show statistical differences among the groups. Corticosterone concentration increased in acute condition for GTI and GTC. Testosterone concentration reduced 71 % in GTC immediately after the exercise in comparison to CG. The GTI allowed positive adaptations when compared to GTC in relation to: glycogen super-compensation, training volume performed and anabolic condition. However, the GTI not improved the aerobic performance.
Keywords: Liver; Animals; kosterní svaly; Anaerobic Threshold; Rats, Wistar; játra; testosteron; Fatty Acids, Nonesterified; běh; kondiční příprava zvířat; fyziologická adaptace; kortikosteron; Corticosterone; Muscle, Skeletal; anaerobní práh; Running; tělesná hmotnost; aerobióza; Male; glukosa; kyseliny mastné neesterifikované; Glucose; Adaptation, Physiological; Aerobiosis; krysa rodu Rattus; Body Weight; Physical Conditioning, Animal; Testosterone; zvířata; mužské pohlaví; Glycogen; Rats; glykogen; potkani Wistar